Seasonal influenza vaccines: Variability of immune responses to B lineage viruses - Matthew S. Miller; Emanuele Montomoli; Eyal Leshem; Michael Schotsaert; Thomas Weinke; Nevena Vicic; Deborah Rudin (Human Vaccines & Immunotherapeutics)
Although influenza A viruses predominate globally, influenza B viruses are responsible for a significant and often underappreciated burden. Despite this, immunity to influenza B viruses remains understudied, and there is a perception that vaccine-mediated immune responses to influenza B strains are less robust than influenza A strains. This targeted literature review examines this concept using data from pivotal phase 3 immunogenicity studies on currently licensed seasonal influenza vaccines and explores several explanations for this phenomenon, including immune exposure history, assay limitations, virus-related properties inherent to B lineages, and strain mismatch. Overall, studies demonstrated vaccines induce variable and sometimes less robust immune responses to influenza B strains; however, further studies are needed to fully confirm and understand these observations. In identifying the potential causes of variable performance of current vaccines against influenza, this review aims to guide vaccine development to enhance overall vaccine performance and reduce disease burden worldwide.